PENINGKATAN KEMAMPUAN TUMBUH TANAMAN JAGUNG (Zea mays L.) PADA KONDISI CEKAMAN KEKERINGAN OLEH JAMUR MIKORIZA ARBUSKULAR - Agustinur Agustinur; Yusran Yusran; Wahyu Harso (Biocelebes, 2018)
Increasing maize production in Indonesia has been efforted regarding to fulfill the need of human and animal foods by utilizing the marginal land which has poor soil and is often dry. Application of Arbuscular Mycorrhizal Fungi as a biofertilizer in marginal land is a suitable alternative to overcome its problems. The aim of this research was to observe the effect of the different amounts of mycorrhizal fungal inoculum application on maize plant growth under different water regimes. Maize plants were inoculated by 0, 15, and 20 gram inoculum from Gigaspora margarita species and grown under soil water content at 60, 40 and 20% of soil fied capacity respectively. The results showed that application of mycorrhizal inoculum increased P absorption and hence plant growth under different water regimes. Plant inoculated by 20 gram inoculum had higher plant growth than plant inoculated by 10 gram inoculum particularly under soil water content at 60% of field capacity however the degree of fungal colonization was not significantly different.